An exploratory clinical study of β-glucan combined with camrelizumab and SOX chemotherapy as first-line treatment for advanced gastric adenocarcinoma - Chu, Yunqian; He, Xuan; Xue, Ya; Jiang, Hua; Zhu, Chan; Qi, Chunjian; Zhang, Xing; Chen, Dongsheng; Dai, Hanjue; Xian, Qingying; Zhu, Wenyu (Frontiers in Immunology, 2024)
Background: β-glucan has been reported to be a potential natural immune modulator for tumor growth inhibition. We aimed to evalute the efficacy and safety of β-glucan plus immunotherapy and chemotherapy in the first-line treatment of advanced gastric adenocarcinoma. Methods: This is a phase IB, prospective, single-arm, investigator-initiated trail. Advanced gastric adenocarcinoma patients received β-glucan, camrelizumab, oxaliplatin, oral S-1 every 3 weeks. The curative effect was evaluated every 2 cycles. The primary endpoints were objective response rate (ORR) and safety, with secondary endpoints were median progression-free survival (mPFS) and median overall survival (mOS). The exploratory endpoint explored biomarkers of response to treatment efficacy. Results: A total of 30 patients had been enrolled, including 20 (66.7%) males and all patients with an ECOG PS score of ≥1. The ORR was 60%, the mPFS was 10.4 months (95% confidence interval [CI], 9.52-11.27), the mOS was 14.0 months (95% CI, 11.09-16.91). A total of 19 patients (63.3%) had TRAEs, with 9 patients (30%) with grade ≥ 3. The most common TRAEs were nausea (53.3%). After 2 cycles of treatment, the levels of IL-2, IFN-γ and CD4+ T cells significantly increased (P < 0.05). Furthermore, biomarker analysis indicated that patient with better response and longer OS exhibited lower GZMA expression at baseline serum. Conclusions: This preliminary study demonstrates that β-glucan plus camrelizumab and SOX chemotherapy offers favorable efficacy and a manageable safety profile in patients with advanced gastric adenocarcinoma, and further studies are needed to verify its efficacy and safety.